PETROGENESIS OF ILMENITE-BEARING SYMPLECTITE XENOLITHS FROM VITIM ALKALINE BASALTS AND YAKUTIAN KIMBERLITES, RUSSIA - Litasov K.D.; Malkovets V.G.; Taylor L.A.; Kostrovitsky S.I. (My University, 2003)
Ilmenite-bearing symplectite, typically ilmenite-clinopyroxene, occurs in rare mantle xenoliths from kimberlite and other alkaline rocks. Two major hypotheses have been proposed for their origin: (1) exolution from high-pressure pyroxene or garnet; and (2) cotectic or eutectic co-precipitation from evolved “proto-kimberlite” melt, producing megacrysts. Here we present new findings about these ilmenite-clinopyroxene symplectites in the Miocene picrobasalts and Pleistocene basanites of the Vitim volcanic field, central Siberia. For comparison, we have described unusual ilmenite-clinopyroxene symplectites from Yakutian kimberlites: the Mary pipe (Kuoisk field) and the Mir pipe (Malo-Botuobinsk field). Symplectite clinopyroxene from Vitim alkaline basalts corresponds to the low-Mg end of the clinopyroxene megacryst trend. They have an Mg# of 70-72 and contain 1.5-2.0 wt% TiO2. Ilmenites from Vitim symplectites are Cr-poor and contain 5.3-6.3 wt% MgO, whereas ilmenites from kimberlite symplectites contain 0.1-1.4 wt% Cr2O3 and 8-13 wt.% MgO. However, trace-element patterns of symplectitic clinopyroxene in both kimberlites and alkaline basalts are similar. Clinopyroxenes from Vitim symplectites have more evolved trace-element patterns (Lan = 3.1-3.8, normalized to primitive mantle) relative to the majority of megacrysts (Lan = 1.0-3.8). Modeling of fractional crystallization of clinopyroxene from alkaline basaltic melt indicates that clinopyroxenes from symplectites correspond to the residual melt fraction of 20-40%, which is high for eutectic crystallization. Symplectites from the Mary pipe can be divided into Cr-rich (Cr2O3cpx = 0.20-0.39 wt.% and Cr2O3ilm = 0.7-1.3 wt%) and Cr poor (Cr2O3cpx = 0.04-0.16 wt.% and Cr2O3ilm = 0.1-0.4 wt.%) subgroups. However trace-element patterns in clinopyroxenes from both groups of symplectites are similar. This may indicate a symplectite origin from different pulses of magma. Cr-enrichment in the Cr-rich group can be related to contamination by adjacent peridotites. Compositional and textural variations in symplectites from both the alkaline basalts and kimberlites reveal similarities in genesis and a clear connection with megacryst assemblages. We suggest that ilmenite-clinopyroxene symplectites characterize the initial stage of simultaneous precipitation of ilmenite and clinopyroxene. They crystallize after the majority of the clinopyroxene megacrysts and before normal Ilm-Cpx intergrowths and ilmenite megacrysts. This indicates a possible cotectic rather than eutectic precipitation of ilmenite and clinopyroxene in symplectites. Pressure and temperature estimations indicate that Ilm-Cpx symplectites from the Mir and Mary kimberlite pipes formed at pressures of 40-50 kbar, whereas those from Vitim basalts formed at lower pressures of 12-17 kbar. Coexisting Fe-Ti oxides in Vitim ilmenites from symplectites and megacrysts suggest equilibration temperatures of 690-1025°C at fO2 = 0.22-1.88 log units below the QFM buffer. This redox state is similar to that of spinel peridotites in the same localities.